Intelligent systems modeling and decision support in bioengineering - Mahfouf, Mahdi (Artech House engineering in medicine & biology series., 2006)
Intelligent systems try to achieve, through the use of computers, what we associate with intelligence - flexible, learning and adaptive activity like we find in the human brain. For the first time, this groundbreaking resource provides a detailed understanding of the analysis, design, and application of new intelligent systems in the biomedical industry. The book covers the three major areas of application in biomedicine, including the modeling and control in human anaesthesia, decision support for critically ill patients in intensive care units, and modeling of humans who are subjected to physiological stress. The culmination of more than 18 years of research, this cutting-edge reference offers practical modeling and control guidance by presenting a combination of simulations, real-time experiments, and actual patient data.